Role of Aggregate Personal Empowerment: Enhancing the Quality of Life of Women Borrowers Bahawalpur, Pakistan - Sana Fayyaz; Sayeed Mohsin Kazmi; Fatima Khurram; Samar Fahd (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2019)
The present study attempts to understand how personal empowerment can be used to improve quality of life in women and can maintain sustainable economic development. It analyzes that personal empowerment is an important determinant for women improving their quality of life. It also shed light on the linkage between the economic development and quality of life. This paper tries to fulfill this gap by expanding the analysis of personal empowerment that seems to provide a practical solution to reduce poverty and to improve quality of life. It can be done through polishing the ability of women in economic decision making, giving freedom of movement and awareness in political socio-cultural conditions. This raises the question whether personal empowerment also leads to better quality of life or not. The survey has been conducted in the Bahawalpur State of Southern Punjab, Pakistan. A cross-sectional primary data of 400 women borrowers of the three microcredit provided banks, namely Khushhali Bank, Tameer Microfinance Bank and NRSP-Bank was obtained to carry out the analysis. Pragmatic substantiation on the relationship between personal empowerment and quality of life is done by doing a multinomial logit model analysis. The findings illustrate that personal empowerment has a significant impact not only on personal development of women but also have an impact on quality of life. The result also demonstrates that personal empowerment is a crucial aspect to attain good quality of life, especially in economically non-developed states.